The Effectiveness of Task-Based Learning (TBL) Models on Improving Students' Problem-Solving Skills - Lestariani, Nurlita (Lombok Institute, 2023)
The Task-Based Learning (TBL) instructional model refers to an approach that emphasizes the presentation of structured tasks progressively, aiming to train students' problem-solving skills from simple to more complex problems. This study applied a quantitative approach using descriptive methods and an ex post facto research design. The research aims to evaluate the effectiveness of implementing the TBL learning model in enhancing students' understanding of concepts and statistical analysis skills. Participants in this study were students taking Statistics in the third semester of the Biology Education program at the State Islamic University of Mataram during the 2022/2023 academic year. The research instruments included a statistical data concept test and statistical analysis practice. Data analysis was conducted descriptively by comparing the mean scores of students' conceptual tests and analysis practices over 11 meetings. The research findings indicate that students' understanding of statistical concepts fluctuates in line with the complexity of the assigned tasks. Additionally, students' statistical analysis skills vary with the difficulty level of the tasks, but a positive trend in students' performance improvement is observed over time.